30 PRACTICAL STEPS TO IMPLEMENT RISK MANAGEMENT 2. FOLLOW THESE STEPS TO INTEGRATE RISK MANAGEMENT INTO DECISION-MAKING, PROCESSES AND CULTURE. Issue 1 (3rd July 2019) - Sidorenko, Alex
ABSTRACT: Over the last 15 years, I have implemented risk management in hundreds of organisations across Europe, Australia and Middle East. Here is a step by step guide how I actually did it. May not work every time and some decision makers will ignore risks no matter what we do, but it did win the Best ERM implementation award in 2014:)))